Is Super-Fast Broadband Negative? An IV-Estimation of the Broadband Effect on Firms' Sales and Employment Level - Martin Nordin; Erik Grenestam; Joakim Gullstrand (Lund University, School of Economics and Management, Department of Economics, 2019)
This study investigates the relationship between super-fast broadband and firms' sales and employment level in Sweden. It is important to learn more about this recent technological change and few studies has explored the impact of super-fast broadband on firm outcomes. We use the previous roll-out of second-generation internet access to identify the effect of third-generation internet access. The early investments in optic fiber where largely core broadband network investments paving the way for later investments in third-generation broadband technology. Municipalities choosing providers who prioritized cheap technology (broadband over telephone lines, DSL) targeting the many, thus fell behind municipalities choosing providers investing in optic fiber. We find heterogeneity in the broadband effect, but the overall effect is negative. This effect may be associated with the roll-out of 4G mobile broadband in 2011; mobile broadband services are a byproduct of optic fiber because mobile broadband is transmitted from the same high capacity fiber-optic base stations. We suggest that the negative effect found is related to internet use at work and the mixing of private and work related internet use.
Keywords: D22; J23; O30; R50; 330; broadband; optic fiber; firm output; employment; regional analysis